A STUDY ON PROBLEMS & PROSPECTS OF OPTION TRADERS IN INDIA: WITH REFERENCE TO STOCK OPTIONS TRADED IN NATIONAL STOCK EXCHANGE (International Journal of Food and Nutritional Sciences, 2021)
The objective of this study is to examine the problems and possibilities encountered with the aid of Indian option traders, with a particular emphasis on inventory options that are traded on the National Stock Exchange. Option contracts are effective risk management tools that allow for the modification of a base asset at a predetermined rate within a specific timeframe.The research seeks to determine the primary troubles Indian traders have while buying and selling option contracts and investigate the possibility of option buying and selling methods lowering the top rate that traders should pay. It also seems to emphasise the importance of returns for holders and writers of alternatives in bullish, impartial, and bearish markets. The study uses a descriptive methodology and distributes a dependent questionnaire to 40 traders as a comfort pattern. The study assesses a number of variables, which include brokerage charges, option premiums, pricing problems, hazard-reward eventualities, trading frequency, timing, entry-go-out selections, and liquidity. The accrued data are analysed using statistical techniques like one-way ANOVA and hypothesis testing. The results are intended to contribute to a higher knowledge of the Indian alternative buying and selling scene by shedding light on the difficulties encountered by option traders and suggesting feasible solutions.